The value of blue-green algae (Spirulina platensis) as a nutritive supplement and toxicant against almond moth [Cadra cautella (Lepidoptera: Pyralidae)]. - Wahidah H Al-Qahtani (Public Library of Science (PLoS), 2021)
Blue-green algae, Spirulina platensis is a well-known algal formulation known for its beneficial effects on the growth and development in several types of organisms. Although it is used as a food supplement, it possesses significant toxic effects on growth and development of organisms. This study assessed the positive/negative impacts of S. platensis on almond moth, Cadra cautella (almond moth) that is a serious pest of date fruits and other grains under laboratory conditions. The S. platensis powder were mixed with diet and newly hatched C. cautella larvae were fed. The larvae were observed on alternate days to record the data. The diet was changed once a week. The S. platensis proved very good nutrition supplement at lower dose. Whereas, moderate and high mortality was noted for 5 and 10% formulations, respectively. Moreover, larval span was significantly altered by different formulations and lower formulation (1%) resulted in shorter larval period compared to the rest of the formulations. Although 33% mortality was recorded under 5% S. platensis formulation, however, the larvae which reached to adult stage, copulated, and females laid more eggs. Furthermore, the highest mortality (90%) was observed under 10% S. platensis formulation and a few larvae reached adult stage; thus, no data on pupal period and reproductive traits was recorded for this formulation. These findings proved that S. platensis can be used as nutritional supplement as well as a toxic substance to manage C. cautella in date storage. However, future studies on this are needed to reach concrete conclusions.